2007
DOI: 10.1523/jneurosci.0183-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Light Regulates Sodium Channel Activity to Dynamically Control Retinal Signaling

Abstract: The retinal network increases its sensitivity in low-light conditions to detect small visual inputs and decreases its sensitivity in brightlight conditions to prevent saturation. However, the cellular mechanisms that adjust visual signaling in the retinal network are not known. Here, we show that voltage-gated sodium channels in bipolar cells dynamically control retinal light sensitivity. In dim conditions, sodium channels amplified light-evoked synaptic responses mediated by cone pathways. Conversely, in brig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 53 publications
1
43
0
Order By: Relevance
“…These findings expand the functional contributions of ipRGCs beyond those already established for circadian, pupillary, and hormonal regulation to a novel role in intraretinal adaptation. Retinal dopamine, released by DA neurons, modulates the function of all major classes of retinal neurons, including photoreceptors and horizontal and bipolar cells in the outer retina (3,5,6). Thus, the excitatory influence of ipRGCs on DA neurons provides a basis for sustained photic signals originating in the innermost layer of the retina to feed back centrifugally to the outer retina, reversing the canonical direction of visual signaling (Fig.…”
Section: Ganglion Cell Efferent Input To Da Neurons: Bidirectional VImentioning
confidence: 99%
See 1 more Smart Citation
“…These findings expand the functional contributions of ipRGCs beyond those already established for circadian, pupillary, and hormonal regulation to a novel role in intraretinal adaptation. Retinal dopamine, released by DA neurons, modulates the function of all major classes of retinal neurons, including photoreceptors and horizontal and bipolar cells in the outer retina (3,5,6). Thus, the excitatory influence of ipRGCs on DA neurons provides a basis for sustained photic signals originating in the innermost layer of the retina to feed back centrifugally to the outer retina, reversing the canonical direction of visual signaling (Fig.…”
Section: Ganglion Cell Efferent Input To Da Neurons: Bidirectional VImentioning
confidence: 99%
“…Through dopaminergic signaling, they restructure retinal function by modulation of chemical and electrical synapses, as well as by modification of the functional properties of retinal neurons, optimizing the encoding of visual stimuli at different levels of illumination (1). DA neurons receive synaptic input in the inner plexiform layer (IPL) of the inner retina and through direct synaptic contacts, or through volume transmission, influence visual signaling by all major classes of retinal neurons, from photoreceptors to ganglion cells (2)(3)(4)(5)(6).…”
mentioning
confidence: 99%
“…Alternatively, ipRGCs may provide a more direct regulation of a particular class of amacrine cell that produces dopamine. Dopamine is released from these cells in response to light [65], and modulates many aspects of retinal function [66][67][68][69][70]. A subset of ipRGCs form a discrete plexus with dopaminergic amacrines [46, 50, 53, 54], and receive synaptic input from them.…”
Section: Intra-retinal Connectivitymentioning
confidence: 99%
“…Here, we show that decrements of visual prepulse strength produces a comparable pattern of effect, demonstrating that our testing conditions are optimal for detecting changes in visual sensitivity. As demonstrated by numerous studies, dopamine is an important chemichal messenger in the sensory visual system (Richfield et al, 1989;Witkovsky, 2004;Brandies and Yehuda, 2008;Kawai et al, 2011) and it was shown to facilitate adaptation to ambient light (Witkovsky, 2004;Nir et al, 2002;Ichinose and Lukasiewicz, 2007), which raises the possibility that deficits we saw in visual PPI may partly be because of reduced sensitivity to the flash light. Closer examination of the temporal pattern of effects of dopamine agonists suggests that this may possibly be the case for D2 agonists.…”
Section: Discussionmentioning
confidence: 80%